Pathophysiology : clinical concepts of disease processes - Price, Sylvia Anderson; Wilson, Lorraine McCarty (St. Louis, Missouri : Mosby Elsevier, 1992)
This fourth edition has been updated and revised to reflect new developments in the field of pathophysiology. The text retains its clinical focus and body systems approach and features an improved organizational format.
General Concepts of Disease: Health Versus Disease p. 3 Heredity, Environment, and Disease: Interaction of Heredity and Environment p. 6 Cellular Injury and Death p. 28 Response of the Body to Injury: Inflammation and Repair p. 38 Response of the Body to Immunologic Challenge p. 61 Response of the Body to Infectious Agents p. 84 Disturbances in Circulation p. 92 Disturbances in Growth, Cellular Proliferation, and Differentiation p. 108 Familiar Allergic Disorders: Anaphylaxis and the Atopic Diseases p. 125 Bronchial Asthma: Allergic and Otherwise p. 137 Atopic Dermatitis and Urticaria p. 148 Autoimmune and Immune Complex-Induced Diseases p. 153 Adverse Reactions to Drugs and Related Substances p. 163 Approaches to Immune Deficiency States p. 168 Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) p. 173 The Composition of Blood and the Monocyte-Macrophage System p. 191 Red Blood Cell Disorders p. 197 White Blood Cell and Plasma Cell Disorders p. 207 Coagulation Disorders p. 225 Fluid and Electrolyte Balance and Assessment p. 239 Disorders of Fluid Volume, Osmolality, and Electrolytes p. 255 Acid-Base Disorders p. 291 Disorders of the Esophagus p. 315 Disorders of the Stomach and Duodenum p. 326 Disorders of the Small Intestine p. 342 Disorders of the Large Intestine p. 358 Disorders of the Liver, Gallbladder, and Pancreas p. 372 Anatomy of the Cardiovascular System p. 409 Physiology of the Cardiovascular System p. 420 Diagnostic Procedures in Cardiovascular Disease p. 432 Coronary Atherosclerotic Disease p. 460 Valvular Heart Disease p. 488 Cardiac Mechanical Dysfunction and Circulatory Support p. 503 Vascular Disease p. 527 Anatomy and Physiology of the Respiratory System p. 555 Diagnostic Procedures in Respiratory Disease p. 571 Cardinal Signs and Symptoms of Respiratory Disease p. 584 Obstructive Patterns of Respiratory Disease p. 590 Restrictive Patterns of Respiratory Disease p. 600 Cardiovascular Disease and the Lung p. 616 Respiratory Failure p. 622 Pulmonary Malignant Neoplasms p. 636 Pulmonary Tuberculosis p. 642 Anatomy and Physiology of the Kidneys and Urinary Tract p. 653 Diagnostic Procedures in Renal Disease p. 677 Chronic Renal Failure p. 691 End-Stage Renal Disease: The Uremic Syndrome p. 723 Treatment of Chronic Renal Failure p. 734 Acute Renal Failure p. 755 Anatomy and Physiology of the Nervous System p. 769 Evaluation of the Neurologic Patient p. 803 Pain p. 818 Cerebrovascular Disease p. 849 Neurologic Disorders With Generalized Symptomatology p. 860 Seizure Disorders p. 877 Central Nervous System Injury p. 884 Central Nervous System Tumors p. 897 Principles of Endocrine and Metabolic Control Mechanisms p. 911 Pituitary Gland Disorders p. 920 Thyroid Gland Disorders p. 928 Adrenal Hypersecretion Disorders p. 937 Adrenal Hyposecretion Disorders p. 951 Pancreas: Glucose Metabolism and Diabetes Mellitus p. 954 Female Reproductive System Disorders p. 969 Male Reproductive System Disorders p. 991 Sexually Transmitted Diseases p. 1005 Anatomy and Physiology of Bones and Joints p. 1021 Fractures and Dislocations p. 1027 Tumors of the Musculoskeletal System p. 1034 Osteoarthritis p. 1039 Rheumatoid Arthritis p. 1043 Systemic Lupus Erythematosus p. 1049 Scleroderma p. 1053 Gout p. 1056 Seronegative Spondyloarthropathies p. 1060 Anatomy and Physiology of the Skin p. 1067 Acne and Related Conditions p. 1073 Eczema and Vascular Disorders p. 1079 Psoriasis and Pityriasis Rosea p. 1086 Cutaneous Infections p. 1089 Tumors of the Skin p. 1099 Lyme Disease and Infestations p. 1107 Answers p. 1111
Includes bibliographical references and index.
Keywords: PHYSIOLOGY, PATHOLOGICAL